Investigation of the effect of probiotic yogurt and fenugreek on allergic asthma - athari, seyyed shamsadin (Archives of Medical Laboratory Sciences, 2020)
Background: Asthma as the variable degrees of airway obstruction is reversible and allergic asthma is a common form of asthma. Yogurt is coagulated milk and fenugreek as a plant is used in traditional medicine. Oral administration of yogurt (as food) can provide probiotic agents that have the main effects on immune responses. In this study, the effect of yogurt and fenugreek on asthma was studied. Materials and Methods: After producing of asthma model in BALB/c mice in 4 groups, groups were treated with yogurt, yogurt-probiotics, and yogurt-fenugreek. At least, total IgE in serum, IL-4, 5, 13 in BAL (Broncho-Alveolar lavage) fluid was measured. Histopathological sections were prepared and eosinophilic infiltration and mucus-secreting were investigated. Results: Eosinophilic infiltration and mucus hyper-secretion were decreased in treated groups. Total IgE in serum was decreased in asthma-yogurt-probiotic and asthma-yogurt-fenugreek groups in comparison with asthmatic and asthma-yogurt groups. The amount of IL-4 in BAL of the asthma-yogurt-fenugreek group was decreased. The amount of IL-5 in BAL of the asthma-yogurt-probiotic and asthma-yogurt-fenugreek groups was decreased. The amount of IL-13 was decreased significantly in three treated groups. Conclusion: This study showed that yogurt with fenugreek and probiotic has a strong effect on suppression of progression of airway inflammation and asthma pathophysiology.